The impact of a small-scale irrigation scheme on malaria transmission in Ziway area, central Ethiopia - Kibret, S.; Alemu, Y.; Boelee, Eline; Tekie, H.; Alemu, D.; Petros, B. (Wiley, 2009)
Objective To assess the impact of a small-scale irrigation scheme in Ziway area, a semi-arid area in the Central Ethiopian Rift Valley, on malaria transmission. method Parasitological, entomological and socio-economic studies were conducted in a village with and a village without irrigation. Blood smear samples were taken from individuals during the dry and wet seasons of 2005 / 2006. Socio-economic data were collected from household heads and key agricultural and health informants through interviews and questionnaires. Larval and adult mosquitoes were sampled during the dry and short wet seasons of 2006. Female anopheline mosquitoes were tested by enzyme-linked immunosorbent assay for blood meal sources and sporozoite infections. results Malaria prevalence was higher in the irrigated village (19%, P < 0.05) than the non-irrigated village (16%). In the irrigated village, malaria prevalence was higher in the dry season than in the wet season while the reverse occurred in the non-irrigated village. Households with access to irrigation had larger farm land sizes and higher incomes, but also higher prevalence of malaria. Larval and adult abundance of the malaria vectors, Anopheles arabiensis and Anopheles pharoensis, was higher in the irrigated than in the non-irrigated village throughout the study period. Furthermore, the abundance of An. pharoensis was significantly higher than that of An. arabiensis during the dry irrigated period of the year. Canal leakage pools, irrigated fields and irrigation canals were the major breeding habitats of the two vector mosquitoes. Plasmodium falciparum sporozoite infection rates of 1.18% and 0.66% were determined for An. arabiensis and An. pharoensis in the irrigated village. Peak biting activities of the vectors occurred before 22:00 h, which is a source of concern that the effectiveness of ITNs may be compromised as the mosquitoes feed on blood before people go to bed. conclusion Irrigation schemes along the Ethiopian Rift Valley may intensify malaria by increasing the level of prevalence during the dry season. To reduce the intensity of malaria transmission in the smallscale irrigation schemes currently in operation in Ethiopia, year-round source reduction by using proper irrigation water management, coupled with health education, needs to be incorporated into the existing malaria control strategies.